Prevalence of Family Planning Practices among Women Influenced by Husband’s Socio Demography and Decision Making - Mardiana Mansor; San, San Oo; Khatijah Lim Abdullah (Penerbit UKM, 2015)
Family planning is an important practice for women as it can help to improve financial and social status. Unwanted pregnancy has negative effects for husband and financial. However, couples married at a late age may not practice family planning because they want to have kids. The aims of this study were to determine the prevalence, factors associated with husband’s socio demography and decision making in family planning practices among women in reproductive age who attended a polyclinic in Serdang, Malaysia. A cross sectional study was conducted on 245 women with a systematic random sampling. Descriptive analysis, Fisher exact and Chi-square tests were conducted to identify the influence of husband’s socio demographic factors and decision making in family planning practices. The prevalence of family planning practices among married women was moderate (53.9%). Family planning practices among women showed significant relationship with the husband’s socio demography which were husband’s race (p = 0.018), religion (p = 0.008) and making decision in family planning (p = 0.002). The husband’s socio demography showed a significant relationship with the prevalence of the wife practicing family planning. This clearly indicates that the husband is the individual that influence the wife to use contraceptive method. Decision making in family planning by both the husband and wife is important in choosing to use contraceptive method. Health promotion in the concept of health education for male contraceptive method such as pamphlet and booklet is important to promote husband involvement in family planning.